Kajian Normatif Pertanggung Jawaban Pidana pada Pelaku Prostitusi Online Pemberlakuan Undang-Undang Nomor 17 Tahun 2011 Tentang Intelijen Negara sebagai Upaya Penguatan Peran Intelijen Negara dan Jaminan Perlindungan Hukum Agen Intelijen - Nikson Yusuf; Yusrianto Kadir; Ibrahim Ahmad (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Intelligence is closely related to the state, because intelligence functions as an important tool and instrument to maintain the security and sovereignty of the state. Intelligence helps the state in identifying, analyzing, and overcoming threats, both from within and outside the country, and supports the formulation of effective security and defense policies so that appropriate steps can be taken to protect national interests. This writing uses a normative legal research method, namely legal research conducted by examining library materials or secondary data, also called doctrinal research, where law is often conceptualized as what is written in laws and regulations (law in books) or conceptualized as rules or norms that are benchmarks for human behavior. Intelligence at the practical level plays a role as the vanguard in the national security system. The provisions of Law Number 17 of 2011 concerning State Intelligence. which is the legal umbrella for intelligence organizers in carrying out intelligence duties and functions, where the essence of state intelligence is the first line in the national security system. Forms of legal protection for Intelligence Agency agents guaranteed by the state include personal protection, family protection, security protection, welfare protection and supervision.